Desarrollo y evaluación de una técnica de PCR en tiempo real para detectar ADN de Histoplasma capsulatum en muestras clínicas - Toranzo, Adriana Inés (2015)
Histoplasma capsulatum var. capsulatum is the etiologic agent of histoplasmosis (HP), a\nsubacute or chronic mycosis which is endemic in Argentina.\nThe aims of this work were: (i) to develop a real-time PCR assay to amplify a H.\ncapsulatum specific ITS1 (internal transcribed spacer) fragment, (ii) to evaluate the utility\nof this real time PCR assay for the diagnosis of HP in blood samples, and (iii) to compare\nthe efficiency of real time PCR with that of a nested PCR (H. capsulatum specific gene\nHcP 100) previously implemented, and currently in use in our laboratory for diagnostic\npurposes.\nA HP case was defined by positive results of culture and /or serum test positive for H.\ncapsulatum, or histopathological findings (intracellular yeast and granulome) consistent for\nH. capsulatum.\nThe real time PCR assay was standardized with the TaqMan? system addressing the ITS1\nregion of H. capsulatum as specific target. The limit of detection was determined using\nserial dilutions of H. capsulatum DNA samples. The specificity was calculated using\nDNAs of fungal species different from H. capsulatum and DNA from several\nmycobacteria. The lower limit of detection was 50 fg and the analytical specificity was\n98.11%.\nWe analyzed clinical specimen obtained from 176 patients between January 2010 and\nDecember 2013. Of these, 85 were HP cases and 91 presented any of several clinical\nconditions requiring a HP differential diagnosis. At least one blood sample was available\nfrom 151 of these patients (77 HP cases, 74 without HP). Clinical specimens other than\nblood were available from the remaining 25 patients (8 HP cases, 17 without HP).\nDiagnostic accuracy was measured using the following parameters: diagnostic sensitivity,\ndiagnostic specificity, positive predictive value (PPV) and negative predictive value\n(NPV). The performance of the real time PCR assay when applied to blood specimens\nalone was compared with performance when applied to any specimen (including blood).\nThe real time PCR showed significantly higher diagnostic sensitivity (84% versus 71%, p\n<0.05), and NPV (86% versus 76%, p <0.05) when tested on blood plus other clinical\nspecimen than when tested on blood specimens alone. The diagnostic specificity and the\nPPV showed no significant variation when adding specimens other than blood.\nThe real time PCR assay was less sensitive (71% and 84% for blood and blood plus other\nspecimen type, respectively) than the nested PCR (84% and 94% for blood and blood plus\nother specimen type, respectively). Both PCRs were fairly specific (> 91%) and the PPV\nwas high (> 90%) regardless of clinical specimen type.\nPCR assays are sensitive and specific for the detection of H. capsulatum in clinical\nspecimens and have good predictive values for the diagnosis of HP. Whenever possible,\nwe suggest to analyze all the clinical specimens available from every patient, in addition to\nblood samples, to maximize the diagnostic efficiency. However, molecular techniques\nmust be confirmed by conventional microbiology, which remains the gold standard for HP\ndiagnosis.